Ornate Torana - Temples of India Project Team (Jio Institute, 2024)
The temple complex has an ornate torana (ornamental gateway). While the arch of the torana is broken, the pillars are still well-preserved. Each pillar depicts three female figures and one male figure on the lower octagonal part of the shaft. The upper portion of the pillars is adorned with loops and chains of bells.